Three-point center-of-gravity calculation for crosshair light sharing PET detector - Eiji Yoshida; Fujino Obata; Taiga Yamaya (Physics in Medicine & Biology, 2026)
Abstract Objective. The crosshair light-sharing (CLS) PET detector acquires time-of-flight (TOF) and depth-of-interaction (DOI) information by looping scintillation light through a window at the top of the crystals and distributing it to two photosensors, but light is typically detected by an average of six photosensors, making center-of-gravity (CoG) calculation essential for crystal identification. Approach. In this work, an improved CLS detector achieved a shorter coincidence resolving time (CRT) by employing a reflector with a thickness comparable to the 0.2 mm photosensor gap, together with a new CoG calculation method specialized for the CLS detector to address the problem that weak signals at deep interaction positions fall below the noise level caused by light leakage. In the improved CLS detector, the reflector thickness was set to 188 μm to approximate the photosensor gap, and the crystal size was optimized accordingly. The developed three-point CoG (3P-CoG) method removes light that does not contribute to position detection by using only the three outputs with the highest detected energies. Main results. For the improved CLS detector, the new reflective material increased light output and contributed to an improvement in the CRT. Applying 3P-CoG enabled clearer separation of all crystals regardless of interaction depth. Furthermore, 3P-CoG improves the DOI resolution by approximately 10%. Finally, 3P-CoG contributes to data-volume reduction because the crystal response remains stable even when the energy threshold is increased. Significance. These results show that a simple 3P-CoG algorithm can improve interaction-position estimation in CLS detectors.